Stabilization of skyrmions in two-dimensional systems with next-nearest-neighbor exchange interactions - Wang, Wenbin; Sun, Jianmin; Li, Hang (Frontiers in Physics, 2022)
We study, in the absence of a magnetic field, the stabilization of skyrmions in a single layer ferromagnet in the presence of second nearest neighbor exchange interactions. The stabilization of skyrmion not only depends on magnetic anisotropy but also the second nearest neighbor exchange interaction. It stabilizes bimeron in the presence of in-plane magnetic anisotropy while it enhances the stabilization of ferromagnetic background in the presence of perpendicular magnetic anisotropy. Numerical simulation shows that the second nearest neighbor exchange interaction is a viable parameter to control the creation and annihilation of skyrmionic states with a small size. This study may open an alternative avenue to the generation, stabilization, and control of magnetic skyrmions in the two dimensional thin films.